2010
DOI: 10.4149/neo_2010_02_135
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 may be a valuable serum tumor marker in patients with colorectal carcinoma

Abstract: The promotion of tumor growth is due to a combination of several mechanisms, including angiogenesis and the abundance of cell-derived inflammatory cytokines. The aim of this study was to investigate the serum levels of interleukin 17 (IL-17) and the expression of p53 and Vascular Endothelial Growth Factor (VEGF), in order to determine the relationship between these markers and serum IL-17 levels in patients with colorectal carcinoma.Serum levels of the proinflammatory cytokine IL-17 in patients with colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 56 publications
1
33
0
3
Order By: Relevance
“…Accumulating evidence indicates that IL-17 expression is aberrant in several human tumors, such as ovarian cancer,9 cervical cancer,10 breast cancer,11 hepatocellular carcinoma,12 esophageal cancer,13 gastric cancer,14 and colorectal cancer 15. But the underlying mechanism of IL-17 in tumor initiation and progression is not yet completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that IL-17 expression is aberrant in several human tumors, such as ovarian cancer,9 cervical cancer,10 breast cancer,11 hepatocellular carcinoma,12 esophageal cancer,13 gastric cancer,14 and colorectal cancer 15. But the underlying mechanism of IL-17 in tumor initiation and progression is not yet completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Radosavljevic et al indicates that IL-17 levels are higher in CRC patients compared to normal controls. 64 This study used the same patient cohort as the Ljujic study. The authors concluded that IL-17 may be a useful tool for CRC diagnosis.…”
mentioning
confidence: 99%
“…Radosavljevic et al have shown that it might act as a valuable tumor marker in patients with CRC by measuring IL-17A levels in the serum samples from CRC patients. 46 In the investigation of IL-17A's effect along human adenoma-carcinoma sequence, we have found that the elevation of IL-17A starts from the adenoma stage, and is related to the severity of dysplasia. Although the expression level of IL-17A at the cancer is even higher, it is not related to the TNM parameters of CRC.…”
mentioning
confidence: 97%
“…44 It is unknown whether IL-17 can enhance the production of IL-8 from CRC cells, however, both IL-17 and IL-8 have been found to be increased in patients with CRC. 5,31,45,46 It is necessary to further investigate whether IL-17A can stimulate IL-8 released from CRC cells in patients with CRC.…”
mentioning
confidence: 99%